Virtual prototyping in the design process of optimized mould gating system for high pressure die casting. Issue 1 (2nd March 2015) - Raffaeli, Roberto; Favi, Claudio; Mandorli, Ferruccio
Abstract : Purpose: – High pressure die casting is a widely used industrial process to manufacture complex-shaped products in light alloys. Virtual prototyping techniques, especially numeric-based simulations of the casting process, allow the die filling process to be evaluated and help faster optimization of the gating system, which is the most critical element of the mould. The purpose of this paper is to present a four step approach to design optimal moulds taking advantage of the simulation tools. Design/methodology/approach: – No formalized method to design an optimal gating system is available yet and the majority of the studies aim to optimize existing geometries or to choose from alternative solutions. Rather than optimizing the geometries of predefined designs by running attempt trials, the proposed approach defines a procedure to position cavities, gating systems and, finally, to determine the whole mould geometry. Findings: – The approach is demonstrated through three different industrial applications. The design of a six-cavity mould for gas cooking burners is reported at first. Then, two test cases, a cup and a radiator, are reported for showing different arrangements of the gating system. The reached quality of the mould design has been assessed using metallographic analyses of the casts. Originality/value: – The design of a mould is strictly correlated to its product and mainly based on a trial-and-error approach. Numerical simulations offer a powerful and not expensive way to study the effectiveness of different die designs and filling processes. The paper proposes a structured approach for the definition of the gating system. It ultimately leads to improvements in both product quality and process productivity, including more effective control of the die filling and die thermal performance.